Effects of CORO2A on Cell Migration and Proliferation and Its Potential Regulatory Network in Breast Cancer - Deng, Jun-Li; Zhang, Hai-Bo; Zeng, Ying; Xu, Yun-Hua; Huang, Ying; Wang, Guo (Frontiers in Oncology, 2020)
Coronin 2A (CORO2A) is a novel component of the N-CoR (nuclear receptor corepressor) complex. Abnormal CORO2A expression is associated with carcinogenesis. We used databases from the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) and analyzed CORO2A expression and gene regulatory network in breast cancer. Expression was analyzed using GEO and UALCAN tools and further validated in breast cancer samples collected in our clinic. The prognostic value of CORO2A was explored by using the GEPIA and UALCAN websites. LinkedOmics was used to identify coexpressed genes associated with CORO2A. After analyzing the intersection of coexpressed genes correlated with CORO2A and differentially expressed genes after CORO2A silencing, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses of the intersecting genes were conducted by using FunRich software. Transwell assays were performed in breast cancer cells to determine the effect of CORO2A on cell migration. MTS, colony formation and cell cycle distribution assays were performed in breast cancer cells to determine the effect of CORO2A on cell proliferation. Gene enrichment analysis was employed to explore the target networks of transcription factors and miRNAs. We found that CORO2A was upregulated and that the elevated expression of CORO2A was associated with poor overall survival in breast cancer patients, especially those with triple-negative breast cancer (TNBC). Further bioinformatics analysis of public sequencing data and our own RNA-Seq data revealed that CORO2A was probably involved in the epithelial-to-mesenchymal transition process and might have a significant effect on the migration of breast cancer cells, which might be mediated via pathways involving several miRNAs and MYC transcription factors. Functionally, the knockdown of CORO2A inhibited cell migration, decreased cell viability and colony formation and induced cell cycle arrest in the G0/G1 phase in breast cancer cells. Our results demonstrate that bioinformatics-based analysis efficiently reveals information about CORO2A expression and its potential regulatory networks in breast cancer, laying a foundation for further mechanistic research on the role of CORO2A in carcinogenesis. Moreover, CORO2A promotes the migration and proliferation of breast cancer cells and may have an important function in breast cancer progression.